Climate and energy misinformation in Taiwan - Liu, John Chung-En; Lee, Chia-Fen (Frontiers in Communication, 2025)
This study examines climate and energy misinformation in Taiwan using data from fact-checkers. Our findings highlight four primary themes: renewable delayism, distrust in power infrastructure, nuclear distraction, and misleading climate action. Renewable delayism exaggerates the limitations and negative impacts of renewable energy, particularly solar power, to delay its adoption. Distrust in power infrastructure spreads fear about the reliability and safety of Taiwan’s electric grid, undermining public confidence in government energy management. Nuclear distraction shifts focus from renewable energy to nuclear power and spreads misinformation about Japan’s nuclear wastewater. Misleading Climate action is a broad category that either caricatures climate advocacy or creates undue anxiety about the consequences of addressing climate change. Much of this misinformation originates from Chinese-speaking cyberspace, with some evidence of state-sponsored operations. These activities erode trust in climate and energy policies, create confusion, and potentially paralyze necessary actions. This study contributes to the broader literature by offering insights from a non-Western context and emphasizing the importance of considering local media environments in tackling climate misinformation.